DISPARITAS PENAFSIRAN HAKIM DALAM TINDAK PIDANA PENIPUAN YANG TIMBUL DARI PERBUATAN WANPRESTASI - Gatot Rachmat Slamet; Syarif Fadillah; Muhammad Fahruddin (Jurnal Hukum Jurisdictie, 2020)
There is a disparity in the interpretation of judges in cases of fraud and default on decisionsbecause in practice there have been many violations committed by one of the parties to theagreement. above is more complicated when there is no understanding among law enforcementofficials in determining the juridical boundaries between Fraud and Default. This research is anormative juridical research with a legal material search. The results showed that the Judges'Interpretation in Fraud Cases Arising From Default Actions in several cases that had beendecided, it appears that the Panel of Judges has a different interpretation regarding the elementsof deception. In the evidentiary practice, there has been inconsistency regarding the interpretation of criminal acts of fraud, especially regarding the elements of deception. There is an inconsistency from the Panel of Judges' disclaimer regarding the criminal act of fraud based on the case studies that occurred, for example in determining whether the fraud occurred before the agreement wasmade or after the agreement was made (tempus delicti).